Effectiveness of hyperbaric oxygen and medical ozone pretreatment against oxidative stress after global cerebral ischemia in rats - Oter, S.; Seyrek, M.; Sadir, S.; Duz, B.; Topal, T.; Kaplan, M.; Obut, S. (Nature Publishing Group, 2009)
[Abstract Not Available]
24th International Symposium on Cerebral Blood Flow and Metabolism/9th International Conference on Quantification of Brain Function with PET -- JUN 29-JUL 03, 2009 -- Chicago, IL
Keywords: Nitric-Oxide; Antioxidant Enzymes; Brain; Tolerance; Cells